2003
DOI: 10.4049/jimmunol.170.1.508
|View full text |Cite
|
Sign up to set email alerts
|

Induction of In Vitro Reprogramming by Toll-Like Receptor (TLR)2 and TLR4 Agonists in Murine Macrophages: Effects of TLR “Homotolerance” Versus “Heterotolerance” on NF-κB Signaling Pathway Components

Abstract: In this study, tolerance induction by preexposure of murine macrophages to Toll-like receptor (TLR)2 and TLR4 agonists was revisited, focusing on the major signaling components associated with NF-κB activation. Pretreatment of macrophages with a pure TLR4 agonist (protein-free Escherichia coli (Ec) LPS) or with TLR2 agonists (Porphyromonas gingivalis LPS or synthetic lipoprotein Pam3Cys) led to suppression of TNF-α secretion, IL-1R-associated kinase-1, and IκB kinase (IKK) kinase activities, c-jun N-terminal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
263
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(290 citation statements)
references
References 73 publications
21
263
0
5
Order By: Relevance
“…Interestingly, although most of the studies investigating ET have been in vitro studies in which macrophages,39, 75 and less so DC,35 are refractory to a second challenge with LPS (“homotolerance”) a few studies have shown that macrophages pre‐exposed to one TLR‐agonist become unresponsive to challenge with another TLR‐agonist (“heterotolerance”). For instance, LPS‐primed macrophages fail to respond to a second challenge with extracts from other Gram‐negative bacteria 37, 64, 76. One study has also shown that LPS‐primed BMDC are heterotolerant to Pam3Cys, an effect controlled by IL ‐ 1 receptor ‐ associated kinase M, which is an intracellular negative regulator of TLR signalling 63.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although most of the studies investigating ET have been in vitro studies in which macrophages,39, 75 and less so DC,35 are refractory to a second challenge with LPS (“homotolerance”) a few studies have shown that macrophages pre‐exposed to one TLR‐agonist become unresponsive to challenge with another TLR‐agonist (“heterotolerance”). For instance, LPS‐primed macrophages fail to respond to a second challenge with extracts from other Gram‐negative bacteria 37, 64, 76. One study has also shown that LPS‐primed BMDC are heterotolerant to Pam3Cys, an effect controlled by IL ‐ 1 receptor ‐ associated kinase M, which is an intracellular negative regulator of TLR signalling 63.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide‐activated macrophages and DC become refractory to further stimulation with LPS,33 a phenomenon known as endotoxin tolerance (ET), which has been attributed to various factors including: (i) the blockade of intracellular signalling events and subsequent gene re‐programming; (ii) up‐regulation of anti‐inflammatory cytokines like interleukin‐10 (IL‐10) and transforming growth factor‐ β (TGF‐ β ); and (iii) down‐regulation of surface expression of the TLR4 receptor 34. The majority of studies in myeloid cells on ET have been conducted using macrophages and have shown decreased phosphorylation levels of NF‐ κ B as well as other signalling molecules such as p38 mitogen‐activated protein kinase (p38 MAPK) and c‐Jun N‐terminal kinase (JNK) while displaying increased levels of phosphorylated extracellular signal‐regulated kinase and IL‐10 secretion 35, 36, 37, 38, 39. In further studies it was shown that previous exposure to LPS led to impaired activation of TANK‐binding kinase 1 (TBK1) and interferon regulatory factor 3 (IRF3) signalling through TIR‐domain‐containing adapter‐inducing interferon‐ β (TRIF) pathway,38, 40 which has been attributed to the lipid A component of LPS 41.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that activation through an endogenous TLR ligand, such as heat-shock proteins (HSPs) (17,47), may predispose the macrophages to heightened activation by subsequent exposure to microbial TLR ligands (48,49). Alternatively, it is also feasible that prior in vivo exposure to potential endogenous TLR-2 or TLR-4 ligands may have induced tolerance to repeat stimulation (50,51), partially reducing the response expected for the level of TLR-2 or TLR-4 expression in some RA patients, and possibly accounting for the lack of association between TLR expression and response to TLR ligand in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the effects in these cell types are in agreement to that what we observed for intestinal mIC cl2 epithelial cells. Tolerance and cross-tolerance between TLR2 and TLR4 upon long-term (24 h) TLR activation has been attributed to changes in expression of TLRs, as well as to the function of several signaling molecules including IRAK-1, NF-B and MAP kinases (Dobrovolskaia et al, 2003;Li et al, 2000Li et al, , 2006Medvedev et al, 2000Medvedev et al, , 2002Otte et al, 2004;Wang et al, 2002). Whether differences in signalling molecules also contribute to the here observed TLR (cross)-regulation upon short-term TLR activation in mIC cl2 cells awaits detailed investigation of the cell signalling dynamics.…”
Section: Discussionmentioning
confidence: 99%